(untitled) (Bangladesh Journal of Medicine, 2013)
Introduction: Without blood there may be no blood transfusion. Without donors there may not any blood. During vasovagal reaction there is chance of accidental fall and injury to blood donor. So improving the safety of the blood donation experience will reduce the donor injuries and increase the blood donation, donation frequency and donor satisfaction. Objective: This study was done to find out the incidence of blood donor reaction- vasovagal reactions among the blood donors attending at transfusion medicine department of Dhaka Medical College Hospital and to improve the donors safety. Methodology: This study was done at Transfusion Medicine Department of Dhaka Medical College Hospital in the period between January 2010 to December 2010. Total 21815 donors of 18 to 55 years of both sexes were selected after reviewing the questionnaire, physical and medical examination and written consent. Donors were observed for 30 minutes after donation. The needle site was covered with a bandage and the donor was directed to keep the bandage on for several hours. Result: In this study, out of 21815 donors 163(8.7%) developed reaction. In163 reactions, 72(44.18%) were in male and 91 (55.82%) were in female donors. Within 20179 male donors, adverse reactions occurred in 72 (0.35%) and within 1636 female donors, adverse reactions occurred in 91 (5.56%) The symptoms were agitation 23 (14.12%), pallor 31 (19.02%), sweating 29 (17.79%), nausea 21 (12.88%), vomiting 38 (23.21%), cold feeling 12(7.36%), loss of consciousness 9(5.52%),i.e. severe reactions were 9(5.53%) and mild to moderate reactions were154 (94.47%). Among the reactions 127 (0.89%) occurred in new donors, 32 (0.49%) occurred in occasional donors and 4 (0.37%) in periodic donors. Conclusion: Vasovagal reactions are more common in female and new donors. DOI: http://dx.doi.org/10.3329/bjmed.v22i2.13589 Bangladesh J Medicine 2011; 22: 47-50